Synthesis and Characterization of Chitosan-Alginate Hydrogel Adsorbent for Paracetamol Removal from Wastewater - Budi, Hastuti; Arsyada, Asna Fikriana; Saptono, Hadi; Soerja, Koesnarpadi; Azlan, Kamari (Trends in Sciences, 2025)
The extensive use of paracetamol has led to the increasing of paracetamol contamination in aquatic ecosystems, posing risks to both human health and the environment. Adsorption is an efficient and cost-effective strategy for addressing paracetamol contamination in the environment. The main target of this study is to develop an efficient and low-cost adsorbent from natural biopolymers derivate for paracetamol removal in wastewater. A Chitosan-Alginate (Chi/Alg) hydrogel was prepared using ionic gelation method by mixing the Alg and Chi solutions in a 4:1 volumetric ratio. The synthesized hydrogel was characterized using Fourier Transform Infrared (FTIR). x-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Differential Thermal-Thermogravimetric (DTA-TGA) analyzer. Batch adsorption tests were conducted to study the effects of pH, contact time, and adsorbate concentration. UV-Vis spectrophotometer was used to measure the concentration of paracetamol in solution. Adsorption isotherm study was also performed to investigate the kinetic and thermodynamic behavior of the adsorption process. The FTIR data showed the vibration of hydroxyl (O-H), carboxyl (C=O) and amine (N-H2) groups. The XRD data showed that Chi/Alg hydrogel has a semicrystalline structure. Analysis SEM showed that modification of Chi/Alg creates a larger pore size than the initial compound. Finally, DTA-TGA data showed that the beads have higher thermal stability. The batch test showed that the optimum adsorption conditions were achieved at pH 6, contact time of 45 min, and adsorbate concentration of 80 mg/L. The kinetic studies revealed that the adsorption process followed pseudo-second order reaction kinetics model and the Freundlich isotherm model. It also indicated a robust adsorption of the membrane, with the reaction rate constant of 0.1368 g/mg.min and adsorption capacity of 67.58 mg/g. The adsorption mechanism occurs via both physical and chemical interactions, with physical interactions predominating. This demonstrates the efficacy of Chi/Alg hydrogel as an adsorbent for the removal of paracetamol from water. HIGHLIGHTS Adding alginate to the chitosan can improve the stability of the Chitosan adsorbent The manufacture of hydrogel beads Chitosan-Alginate is made by ionic gelation method The adsorbent showed different removal behavior depending on the paracetamol concentration and the length of contact time between the adsorbent and paracetamol. Adsorbent adsorb paracetamol in waste water through chemical and physical mechanisms. The adsorbent maintained over 82.9% efficiency for adsorption of paracetamol in wastewater GRAPHICAL ABSTRACT